Acuerdos de empleo y pactos locales: el pacto por el empleo del Vallés occidental. - Jódar, Pere; Alós-moner, R. de; Martín Artiles, Antonio (Cuadernos de Relaciones Laborales, 2000)
Das artille on employment paris al company level shaw a mor/el of new contents in collective bargaining, linkingemployment withflexiblility of working time, moderation of wages and competitiveness. For this reason this kind q/fta cts are denominated as "Elexecurity A/so Local Employment Pacís al `~ ¡ Ls/a ponen ci cl fue presentada el 28 de Oc/ubre en Bruselas en ci Seminario LA NECOCÍTATION COLLECIIVE DANS LA GOSTRUCTION DE LA NORME SOCIAL DE L'EMJ'LOL, oíganízadopo,-eílns/hnto SiíídicatEuíapeo, de la Confedenzcitin Europea de Sind,cw/cz.r. Los autores, Martín Artítcs y Rajada De Alós son Profisores del Dcpaulam ¡it de Sociologia, (Tnn'eit/at An/ononia Barcelona, Crup Y 5/udis (¿UIT. YPe¡eJ¿dar es profesor del Depar/a¡neo/a de Ciencias Polí/icas y Sociología de la Universidad Pompetí [`abra de Ba,relona. (uade,,ío de Re/cíc:icníes Lzíbo,-ales 207 2000, [7: 207-224 Martín Artjles, A.; De Alós-Monen II.; Jóda¡; Pepe Acuerdos dc empleo y paclos locales:... territorial level coníd extent it Jo another companies aud sectors. This are tite main meanzng of "best firactices".
Keywords: Pact; En¿ployment; Local employment pacts; Elexecurity; flexÑ bility of working time; moderation oJwages; competitiveness